2019
DOI: 10.1111/psj.12332
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization of Islam in Secular Europe: The Influence of State–Religion Relations on Anti‐Muslim Attitudes

Abstract: This study examines church–state relations in Europe, and analyzes their influence on anti‐immigrant attitudes. The literature explains this relationship primarily with religious demographics, or state privileges for the majority faith. Alternately, this study focuses on the status of the majority religion. It argues that, in countries with a national church, citizens are more likely to consider the institutionalization of a new religion to be occurring at the expense of the national heritage, and react negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, the negative attitudes have increased considerably in Eastern Europe, not necessarily for being Muslims but for being immigrants who are perceived to be competing with Eastern Europeans over job opportunities. Research findings by Kaya, 2019 explained the contradiction between Western and Eastern Europeans' attitudes toward Muslim immigrants in religious terms. The findings showed that despite the decline in individual religiosity in Europe, the European countries with a high-profile presence and influence of a national church may lead to rejection of Muslim immigrants and increasing anti-Islam and anti-Muslim immigrant…”
Section: Discussionmentioning
confidence: 88%
“…Meanwhile, the negative attitudes have increased considerably in Eastern Europe, not necessarily for being Muslims but for being immigrants who are perceived to be competing with Eastern Europeans over job opportunities. Research findings by Kaya, 2019 explained the contradiction between Western and Eastern Europeans' attitudes toward Muslim immigrants in religious terms. The findings showed that despite the decline in individual religiosity in Europe, the European countries with a high-profile presence and influence of a national church may lead to rejection of Muslim immigrants and increasing anti-Islam and anti-Muslim immigrant…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the models control for the individual‐ and country‐level factors related to ethnonationalism and attitudes toward Muslims (Arzheimer 2018; Doebler 2014; Gesthuizen et al. 2021; Kaya 2019; Lucassen and Lubbers 2012). On the individual level, controls include age, gender, urban/rural residence, employment status, social class (in the EGP Scheme, missing values as a separate category), educational years, and trust in political institutions (tapping four items).…”
Section: Methodsmentioning
confidence: 99%
“…Further, Kaya () shows how wide the net of “immigrant‐related policies” can get, looking at the institutionalization of Islam as a function of the strength of a national church. This scholarship illustrates the importance of “constructing‐up” integration policy, as well as how the distinctions between and content of integration and immigration policy may differ across national settings, owing not only to national definitions of immigration policy but also the ethnic composition of immigrant groups.…”
Section: Theory Development and Testingmentioning
confidence: 99%